CURRENT TRENDS IN NEONATAL SURGERY IN INDIA - Yogesh Kumar Sarin; Sushmita N Bhatnagar (EL-Med-Pub, 2012)
Neonatal surgery is a highly specialized and the most sophisticated field of Pediatric Surgery. It is indeed the jewel in the crown of our specialty. The exact status of neonatal surgery in India has been scantly documented. Gupta et al had concluded a decade ago that the results of surgery for the same condition were very variable in different centers. The reasons for poor survival were diverse, but it was noticed that the amount of work load inversely correlated with the results. In spite of sophistication in technology, they observed that the overall survival rates in India were far inferior to that noted in the centers from the developed world.